Under the baseball moon - Ritter, John H., 1951- (New York : Philomel Books, 2006)
Andy and Glory, two fifteen-year-olds from Ocean Beach, California, pursue their respective dreams of becoming a famous musician and a professional softball player.
Keywords: Softball -- Fiction; Trumpet -- Fiction; Musicians -- Fiction; Interpersonal relations -- Fiction; California -- Fiction